Analysis of the determinants of income and income gap between urban and rural China - Biwei Su; Almas Heshmati (Institute for the Study of Labor (IZA), 2013)
This paper studies on the determinants of income and urban-rural income gap to shed light on the problem of urban-rural income inequality in China. OLS, conditional quantile regression and Blinder-Oaxaca decomposition methods are used to analyze four waves of the China Health and Nutrition Survey (CHNS) household data. Results show that education and occupation are essential determinants of households' income level. These two factors exert heterogeneous effects at different percentiles of the income distribution. In urban areas, education is more valued for high income earners, while for rural areas, specialized or tertiary education are more beneficial for the poorer households. Among all occupational types, farm activities show much lower returns than other types; and this is more evident for individuals at the left tail of the income distribution. We also find that for the sampled provinces, urban-rural income gap increases from the year of 2000 to 2004 but the gap decreases from 2004 to 2009. The income gap can be largely explained by the individuals' attributes, especially by level of education and type of occupation.
Keywords: O15; O18; D31; D63; C31; 330; urban-rural income gap; Oaxaca-Blinder decomposition; quantile regression; CHNS household data; China